Morphological and molecular characterization of Discocriconemella inarata, an endemic nematode from north american native tallgrass prairies - Powers, Thomas O (Journal of nematology, 2010)
Discocriconemella inarata, a plant parasitic nematode species originally discovered in a virgin tallgrass prairie in northwest Iowa, was re-examined by molecular and morphological analyses of topotype material. This species has never been recorded in cultivated fields and could potentially serve as an indicator for high quality prairie habitats. DNA sequence from a conserved 3' portion of the 18S ribosomal gene exhibited an identical match between D. inarata topotype specimens and topotype specimens of Mesocriconema xenoplax from Fresno, California. Higher resolution sequence analyses using the internal transcribed spacer 1 (ITS1) and a portion of the mitochondrial gene cytochrome b (cytb) allowed discrimination of D. inarata apart from M. xenoplax. This pair of species formed a well-supported clade with other Mesocriconema species exclusive of tropical Discocriconemella species. Scanning electron microscopy confirmed the absence of submedian lobes on D. inarata, suggesting a secondary loss of this defining morphological characteristic for Mesocriconema. Observations and measurements of D. inarata juveniles were added for the first time. Surveys of other prairies within the Great Plains expanded the known distribution of this species